2013
DOI: 10.1021/jz401207z
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of para-Xylylene as the Decomposition Product of the meta-Xylyl Radical Using VUV Synchrotron Radiation

Abstract: Xylyl (methylbenzyl) radicals are important combustion intermediates, formed in the pyrolysis and oxidation of xylenes and other substituted aromatic fuel additives. We have used VUV synchrotron radiation and imaging photoelectron photoion coincidence (iPEPICO) spectroscopy techniques to identify para-xylylene as the dominant stable C 8 H 8 product arising from thermal decomposition of the meta-xylyl radical. A complex rearrangement from a meta-to a para-substituted aromatic, supported by quantum chemical cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 33 publications
4
60
1
1
Order By: Relevance
“…So, the presence of o -xylylene, which has a lower ionization energy than p -xylylene, can be excluded at this position of the flame (6.5 mm). Similar observations were also made in a heated SiC reactor in previous work by Hemberger et al [14,15] , where different reactor temperatures showed different C 8 H 8 isomer compositions depending also on the prepared xylyl radical. The TPE spectrum of m/z = 104 obtained from pyrolysis of m -xylyl bromide at 1300 K surface temperature is also shown in Fig.…”
Section: Decomposition Of M -Xylenesupporting
confidence: 87%
See 4 more Smart Citations
“…So, the presence of o -xylylene, which has a lower ionization energy than p -xylylene, can be excluded at this position of the flame (6.5 mm). Similar observations were also made in a heated SiC reactor in previous work by Hemberger et al [14,15] , where different reactor temperatures showed different C 8 H 8 isomer compositions depending also on the prepared xylyl radical. The TPE spectrum of m/z = 104 obtained from pyrolysis of m -xylyl bromide at 1300 K surface temperature is also shown in Fig.…”
Section: Decomposition Of M -Xylenesupporting
confidence: 87%
“…The presence of benzocyclobutene indicates that this reaction also occurs here, although the o -xylylene could not be detected. Benzocyclobutene itself isomerizes to styrene [14,38] and was identified by the peak at 8.66 eV which matches the measured and calculated value of the adiabatic ionization energy of 8.65 eV [15] . Styrene can be found with the highest concentration of all C 8 H 8 isomers (the maximum mole fraction is twice that of pxylylene).…”
Section: Decomposition Of M -Xylenesupporting
confidence: 74%
See 3 more Smart Citations